Pelatihan Pengelolaan Keuangan Untuk Meningkatkan Kemampuan Perencanaan Keuangan Keluarga - Ummi Kalsum; Randy Hidayat; Belliwati Kosim; Arradytia Permana (Jurnal Pengabdian UntukMu NegeRI, 2022)
Abstract Managing family finances is a fundamental skill that every household must understand. In general, financial problems that often occur are when expenses are greater than the amount of income earned, and the amount of income received is irregular. Through this financial management training, which aims to make participants able to identify sources of income and expenses, be able to determine spending priorities and write them down in the family budget and understand how to control spending in accordance with the budget that has been prepared so that family needs can be met. The implementation of this training activity on February 29, 2022 at PAUD Islam Salsabila Palembang with 25 participants from parents and teachers. This training activity was quite successful considering that all participants were able to prepare budgets and record cash flows.